EDUCATION POLICY ANALYSIS IN ORDER TO IMPROVE TEACHER PROFESSIONALISM - Nuraeni Nuraeni; I Wayan Widiana; I Gede Ratnaya (CV. Syntax Corporation Indonesia, 2023)
Teacher professionalism can be seen from its role in carrying out tasks, namely developing the potential of students with heterogeneous backgrounds, both basic abilities, social, economic and cultural. Today's teacher professionalism is still included in the